Implications of School Leadership and Policy: Principals' Perspectives - Muhammad Ikhsan Butarbutar; Inom Nasution (Program Magister Manajemen Pendidikan Islam Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2024)
This research is to determine the leadership experience and knowledge of school principals, the influence of principal leadership, and also the principal's policies. Semi-structured interviews are designed based on theoretical studies to find the data needed. Interview data was transcribed and reviewed using a thematic content analysis system. This research uses a qualitative research type of phenomenological method. The indicators in this research are, providing rewards, evaluating decisions, and teacher performance. This study emphasizes the importance of principal leadership, the influence of school leadership, and principal policies in achieving the school vision. The results of this research are that the principal as the main leader of the school plays a role in directing, compiling, planning, organizing and supervising in accordance with the school's goals. By knowing and carrying out this leadership role correctly, the school principal will be able to lead the institution he leads well. Effective leadership must possess qualities that positively influence the progress of the school, and policies implemented by the principal should contribute to achieving academic excellence and advancing the school's mission.